Penerapan Model Project-Based Learning dengan Pendekatan STEAM untuk Meningkatkan Keterampilan Berpikir Kritis Siswa pada Materi Energi Alternatif - Azzahra Salsabila; Hera Novia; Ida Kaniawati (Mataram University, 2026)
Critical thinking is recognized as a fundamental competency among the essential skills required in the 21st century. However, students' critical thinking skills have not yet developed optimally, highlighting the need for instructional models that actively engage students throughout the learning process. One approach to fostering active student engagement is the implementation of the Project-Based Learning (PjBL) model integrated with the STEAM approach. This study employed a quantitative quasi-experimental method using a pretest–posttest non-equivalent control group design. The sample consisted of 62 tenth-grade students from a public senior high school in Bandung, Indonesia. The research instrument comprised nine essay questions designed to assess students' critical thinking skills. The data were analyzed using the normalized gain (N-Gain) to determine the improvement in critical thinking skills, while the Mann–Whitney U test was employed to examine the effect of the instructional model. The findings revealed that the improvement in students' critical thinking skills in the experimental class was higher than that of the control class, with N-Gain scores of 0.471 and 0.342, respectively, both of which were classified as moderate. Furthermore, the Mann–Whitney U test at the 5% significance level indicated a statistically significant difference between the two groups. Therefore, it can be concluded that the implementation of the Project-Based Learning model integrated with the STEAM approach has a significant positive effect on improving students' critical thinking skills in the topic of Alternative Energy.